Development of media animated video to improve learning outcomes of Sunda siger bridal makeup - Siti Wahida; Marnala Tobing; Astrid Sitompul (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The teaching and learning process for cosmetology education students needs to be developed to provide meaningful experiences in the learning process both in theory and practice, as well as being able to provide solutions to the problems found to improve learning outcomes and creativity, one of which is in the Sunda siger bridal makeup learning material. The development model refers to Research and development (R&D) and the Borg & Gall model. The development research results show that video-based learning media exists in the Indonesian bridal makeup course, especially in the Sunda Siger bridal makeup learning material, with an average feasibility level based on the expert judgment of 80.15% declared feasible. A small and wide class trial is carried out with the same score of 80,4% declared eligible. The feasibility results obtained from experts and trials analyzed for data, the acquisition of the control class scores with the results of the pretest 64% and posttest 75.67%, in the experimental class, the value of the pretest was 71.57%, and the posttest was 88.33%, from the results of the use value. This video media is suitable for learning about Sunda siger bridal makeup. The results of the media being accepted or rejected can be seen from the value of the t-test where the learning video media obtained tcount 24.54 and t-table 2,086, with the acquisition of t-count greater than t-table then H1 accepted video media in the development of video media in learning Sunda siger bridal makeup.